2011
DOI: 10.1259/bjr/47164832
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with nodal metastasis in nasopharyngeal cancer: an approach to reduce the radiation field in selected patients

Abstract: Objectives: The purpose of this study was to investigate factors associated with lymph node (LN) metastasis to identify which nasopharyngeal cancer (NPC) patients can undergo a reduction in the prophylactic radiation field. MRI of biopsy-proven NPC patients was evaluated to determine primary tumour extension and the existence of LN metastasis. Methods: Sex, age, pathological type, T stage, primary tumour size, existence beyond the midline of the nasopharynx at the primary site and parapharyngeal extension of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
9
10
0
Order By: Relevance
“…Only 1 patient (<1%) had contralateral CLN metastasis to level Va without contralateral retropharyngeal or level II metastasis. Our result further confirmed the findings of Tomita et al…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Only 1 patient (<1%) had contralateral CLN metastasis to level Va without contralateral retropharyngeal or level II metastasis. Our result further confirmed the findings of Tomita et al…”
Section: Discussionsupporting
confidence: 93%
“…The above characteristic patterns of lymph node metastasis were not significantly associated with any potential risk factor, including age, sex, involved laterality, T classification, tumor volume, ipsilateral retropharyngeal lymph node involvement, ipsilateral CLN involvement, ipsilateral retropharyngeal lymph node or CLN involvement, and ipsilateral retropharyngeal lymph node and CLN involvement. A previous study showed that tumors that infiltrate beyond the midline or World Health Organization (WHO) pathological type II/III disease were more likely to metastasize to the bilateral neck than tumors limited to the lateralized nasopharynx or WHO pathological I disease ( p < .05), whereas age, sex, T classification, parapharyngeal invasion, and tumor size were not significant risk factors for bilateral lymph node metastasis . In this study, we analyzed risk factors in patients with lateralized cancer of the nasopharynx, all of whom were patients with WHO pathological type II/III disease.…”
Section: Discussionmentioning
confidence: 93%
“…Our results confirm that LN metastasis spreads from upper neck to lower neck, and skip metastasis is unusual, which concurs with the findings of Tang et al [25]. Tomita et al [28] investigated the pattern of LN metastasis in unilateral NPC and found that the involvement rates of contralateral RLN and level II were 10% and 16%, respectively, whereas less than 3% of patients had involvement of contralateral levels III, IV, and/or V. Thus, the authors indicated that contralateral LN areas other than RLN and level II could be omitted in patients with unilateral NPC. In this study, 94% of patients had bilateral NPC, and the relationship between the laterality of local disease and LN metastasis was not analyzed.…”
Section: Discussionsupporting
confidence: 93%
“…29 In the case of NPC, the lymphatic vessels of the nasopharynx drain in two general directions, laterally and medially. 31 Our study further confirmed these findings. 31 Our study further confirmed these findings.…”
Section: Discussionsupporting
confidence: 86%
“…30 Previous studies reported that most patients with lateralized cancer of the nasopharynx had no LN metastasis or only ipsilateral LN metastasis to the RP and/or level II. 31 EBV-DNA positivity was another risk factor associated with tumour infiltration of the CPR. In this study, 62.5% of the patients with lateral cancer of the nasopharynx had ipsilateral LN metastasis, and no patients had contralateral LN metastasis only.…”
Section: Discussionmentioning
confidence: 93%